PERANCANGAN MEDIA PROMOSI PRODUKAP GUITARS MELALUI AUDIO VISUAL - Suharto Suharto; Moh Sofwan Syauri; Tristan Alfian; Dwi Agus Susila (SULUH: Jurnal Seni Desain Budaya, 2021)
AP Guitars company produces the guitar, the uniqueness of this guitar is the design shape of the neck and head of the guitar which has a V-shaped guitar neck contour and there are carvings to decorate and company character. Due to the lack of promotion of the media used to promote, it is necessary to have a more effective promotional media through Audio Visual media to attract potential consumers and introduce them to the wider community. The design of the AP Guitars Product Promotion Video uses a qualitative method as a source in collecting AP Guitars Product Promotion Video Design using the delivery of messages in the form of Audio Visual with the concept of Video Mapping, namely by highlighting objects or products with a monitor screen whose visuals have been adjusted to the highlighted product. The supporting media used to support the main media in the form of audio visual consists of posters, x-banners, tshirts, price tags, guitar straps, guitar bags, guitar picks, and product catalog books ..Audio visual works that have been created will be uploaded through the channel. youtube company AP guitars as promotional media